A Description of the Life and Works of Abul Fazl Al-Hamadhani by Abu Mansur Al-Saolibi (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
In article investigation philosopfcal-artistie views in the letters and the poems by Abul Fazl al Hamadoni which lifed in middle X century and in beginning XI century.